THE SECOND STAGE OF STUDY OF ANTARCTICA SINCE THE END OF THE 19TH CENTURY TO THE START OF THE SECOND WORLD WAR (VTOROI ETAP IZUCHENIYA ANTARKTIKI S KONTSA XIX VEKA DO NACHALA VTOROI MIROVOI VOINY0 - Tkachenko,B. V. (1968)
The report contains a study of the start of the second stage of investigations in Antarctica. Scientific results of expeditions, history and planned exploration is given. Trans. of Nauchno-Issledovatelskii Institut Geologii Arktiki. Trudy (USSR) v95 p15-39 1957.